One-pot synthesis of 2-trifluoromethylchromones - Henao Castañeda, Isabel Cristina (2011)
We report a simple and suitable method for the preparation of useful 2-trifluoromethylchromones in one step, in high yields and avoiding the use of solvents. We were able to detect the intermediate of this reaction. Furthermore a mechanism for the formation of the 7-methoxy-3-trifluoroacetyl-2-trifluoromethylchromone through the unexpected double trifluoroacetylation of 4-methoxy-2- hydroxyacetophenone followed by dehydration is also proposed. All compounds are fully identified and characterized by spectroscopic techniques.